2020
DOI: 10.1002/jclp.22973
|View full text |Cite
|
Sign up to set email alerts
|

Psychological pain and previous suicide attempts in young adults: Results with the Portuguese version of the Psychache Scale

Abstract: Objectives In this study, we tested whether the unbearable pain scale of the Psychache Scale provides value for the statistical prediction of a previous suicide attempt; we evaluated whether psychological pain has incremental value in the statistical prediction of a previous suicide attempt relative to the reporting of having had a psychiatric diagnosis, and we established a cut‐score for the Psychache Scale. Method Two samples participated: a sample consisting of 1,460 young adults and a sample of 628 Portugu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Results showed that adolescents in the pain avoidance class (at baseline) had the highest OR of probability in SA class, while those in the painful feelings class reported no higher OR in NSSI class, indicating the specific predicting role of pain avoidance on SA. This result was supported by a previous study showing that psychological pain significantly predicted the history of SA in adults (Campos & Holden, 2020) or 10 weeks later in undergraduates (Lambert et al, 2020). Furthermore, compared to painful feelings class, adolescents in pain avoidance class reported 15.56 OR of probability in SA, indicating that pain avoidance had more predictive power on SA than painful feelings.…”
Section: Discussionsupporting
confidence: 82%
“…Results showed that adolescents in the pain avoidance class (at baseline) had the highest OR of probability in SA class, while those in the painful feelings class reported no higher OR in NSSI class, indicating the specific predicting role of pain avoidance on SA. This result was supported by a previous study showing that psychological pain significantly predicted the history of SA in adults (Campos & Holden, 2020) or 10 weeks later in undergraduates (Lambert et al, 2020). Furthermore, compared to painful feelings class, adolescents in pain avoidance class reported 15.56 OR of probability in SA, indicating that pain avoidance had more predictive power on SA than painful feelings.…”
Section: Discussionsupporting
confidence: 82%
“…Because respondents who are willing to take part in the study could be more optimistic than those who refused our survey. Fifthly, although prior studies have established a strong correlation between psychological pain and suicide-related variables [ [6] , [7] , [8] , [9] , [10] ], we did not conduct the measurements of the relationship to enhance the strength of the evidence supporting. Finally, the questionnaire is not entirely an objective research tool.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobiological evidence also suggests that psychological pain may be related to cognitive decline [ 5 ]. Additionally, it is noted that previous studies demonstrate robust associations between psychological pain and suicide [ [6] , [7] , [8] , [9] , [10] ], as severe psychological pain can serve as a primary motivation and impetus for suicide [ 3 , 11 ]. Chronic psychological pain can lead to a variety of psychological health problems associated with suicide risk such as depression, anxiety, personality disorders [ 12 ], and can weaken an individual's coping abilities, making it difficult for them to effectively cope with life's difficulties and pressures, which can lead them to consider suicide as a means of escaping reality [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults die by suicide at a higher rate than any other age group in nearly every country globally [18]. Noteworthy is the fact that psychache has been particularly associated with suicide ideation and attempts [19]. The rates of suicidal thoughts and attempts are higher in patients with high psychological pain.…”
Section: Introductionmentioning
confidence: 99%